1974
DOI: 10.1084/jem.139.6.1395
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Control of Lysosomal Enzyme Release From Human Neutrophils

Abstract: Release of lysosomal enzymes from phagocytic leukocytes in the presence of various immune reactants is well documented (1-6). The tissue injury that results from the accumulation of, and phagocytosis by, granulocytes is probably a direct consequence of the extracellular release of granule constituents (7,8). Indeed, lysosome granules proteins are capable of mediating inflammation (9, 10) and cartilage degradation (11-13).The anti-inflammatory action of certain catecholamines in various animal models of acute (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

1974
1974
1993
1993

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…Previous reports from this laboratory indicated that acetylcholine enhanced whereas epinephrine inhibited the immunologic discharge of lysosomal enzymes from human mixed leukocytes (1) and purified neutrophils (3,4). However, the precise time-course of release of/3-glucuronidase under these conditions was not reported.…”
Section: Effects Of Zymosan a Cetylcholine And Epinephrine On Concementioning
confidence: 63%
See 4 more Smart Citations
“…Previous reports from this laboratory indicated that acetylcholine enhanced whereas epinephrine inhibited the immunologic discharge of lysosomal enzymes from human mixed leukocytes (1) and purified neutrophils (3,4). However, the precise time-course of release of/3-glucuronidase under these conditions was not reported.…”
Section: Effects Of Zymosan a Cetylcholine And Epinephrine On Concementioning
confidence: 63%
“…Cells (5 X 106) were preincubated in 1.0 ml of Hanks'-glucose at 37°C for 10 rain before the addition of 4 X 108 zymosan particles and then further incubated at 37°C for 10 min. Under these experimental conditions phagocytosis of particles occurred and/3-glucuronidase was discharged into the extracellular medium (4). Contact of cells with zymosan particles provoked a marked elevation of cyclic GMP levels but no change in cyclic AMP levels in neutrophils (Fig.…”
Section: Effects Of Zymosan a Cetylcholine And Epinephrine On Concementioning
confidence: 99%
See 3 more Smart Citations